Integrating Indian Knowledge Systems in Contemporary Education: A Theoretical Analysis of NEP 2020 - Sarita; Singh, Damanpreet (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The National Education Policy (NEP) 2020 marks a paradigm shift in the Indian education system by emphasizing holistic development, multidisciplinary learning, and the integration of Indian Knowledge Systems (IKS). This theoretical paper explores how NEP 2020 envisions the inclusion of IKS such as yoga, Ayurveda, indigenous games, ethics, and classical languages into contemporary education. It highlights the policy’s emphasis on balancing modern scientific learning with India’s rich cultural and philosophical traditions. The study discusses the theoretical framework of IKS, its provisions under NEP 2020, challenges of implementation, and the potential for creating a globally relevant yet rooted education system. The paper argues that the effective integration of IKS will not only strengthen cultural identity but also promote holistic, inclusive, and sustainable human development.